Enhanced Coupling Between Soft Ferromagnetism and Displacive Ferroelectricity in the Pb‐Site Modified PbFe1/2Nb1/2O3 - Ji‐Hun Park; Jae‐Hyeon Cho; Nyun Jong Lee; Hyun‐Jae Lee; Ju‐Hyeon Lee; Geon‐Ju Lee; Frederick P. Marlton; Motohiro Suzuki; Manuel Hinterstein; Yoon Seok Oh; Ji‐Won Choi; Geon‐Tae Hwang; et al. (Advanced Electronic Materials)
Abstract Albeit having great potential toward unprecedented type of applications such as magnetoelectric (ME) sensors and memories, practically useful single‐phase multiferroics that show large coupling between ferromagnetism and ferroelectricity at ambient temperatures are still lacking. Here, the discovery of a new type of perovskite ferroelectrics (Pb,M)(Fe1/2Nb1/2)O3 (M = Fe, Co, Ni) is reported with a magnetically‐active metal ion introduced into a cuboctahedrally‐coordinated Pb position, which exhibits enhanced ME coupling owing to the development of simultaneous soft‐ferromagnetism and lone‐pair ferroelectricity persistent above room temperature. These Pb‐site engineered (Pb,M)(Fe1/2Nb1/2)O3 perovskites exhibit a ME coupling coefficient of ≈40–60 ps m−1, a saturated electric polarization of 14–17 µC cm−2 and a saturation magnetization of 0.15–0.3 µB f.u−1. X‐ray absorption spectroscopy combined with first‐principles calculations demonstrates that the induced ferromagnetism originates from the ferromagnetic superexchange interaction coming from ≈90° bonding between the magnetic ions at the Pb site. The present discovery of the enhanced ME coupling in the Pb‐site engineered perovskite ferroelectrics may provide unforeseen opportunities for applying conventional displacive ferroelectricity in the field of spintronics where ferromagnetism is essentially required.